2016
DOI: 10.1007/s10683-015-9475-7
|View full text |Cite
|
Sign up to set email alerts
|

Strong, bold, and kind: self-control and cooperation in social dilemmas

Abstract: We develop a model relating self-control, risk preferences and conflict identification to cooperation patterns in social dilemmas. We subject our model to data from an experimental public goods game and a risk experiment, and we measure conflict identification and self-control.As predicted, we find a robust association between self-control and higher levels of cooperation, and the association is weaker for more risk-averse individuals. Free riders differ from other contributor types only in their tendency not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 88 publications
12
27
1
Order By: Relevance
“…In a one-shot, linear public good game, Kocher et al (2012) tested a model of the relation between cooperation, self-control, risk-preferences, and the contributions of other players. Consistent with predictions from their model, cooperation are positively associated with the Rosenbaum (1980a) measure of trait self-control, and this association is moderated by risk-preferenceshigher risk aversion implies a weaker association.…”
Section: Self-control and Social Dilemmasmentioning
confidence: 99%
See 2 more Smart Citations
“…In a one-shot, linear public good game, Kocher et al (2012) tested a model of the relation between cooperation, self-control, risk-preferences, and the contributions of other players. Consistent with predictions from their model, cooperation are positively associated with the Rosenbaum (1980a) measure of trait self-control, and this association is moderated by risk-preferenceshigher risk aversion implies a weaker association.…”
Section: Self-control and Social Dilemmasmentioning
confidence: 99%
“…They found that capacity for self-control was positively related to cooperation among participants who reported feeling conflicted during the contribution decision, but not among participants who reported no conflict. Our present paper seeks to test the causality of conflict identification in the public good, unresolved in Kocher et al (2012), by importing the experimental treatment from the dictator game by Martinsson et al (2010). We also included the conflict measure from Kocher et al (2012) to verify the treatment and to replicate the pattern obtained by them.…”
Section: Measurement Of Conflict Identification and Of Trait Self-conmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity in these preferences has been linked to a number of demographic attributes (Andreoni and Vesterlund, 2001;List, 2004), personality traits (Volk et al, 2012) as well as differences in beliefs (Fischbacher and Gächter, 2010). Recent experimental evidence (Piovesan and Wengström, 2009;Kocher et al, 2012;Rand et al, 2012;Duffy and Smith, 2012;Nielsen et al, 2014) suggests that the extent of cooperative behavior is additionally influenced by the type of cognitive system that potential contributors employ when considering their contribution choice. Two principal types of cognitive systems are distinguished by the reigning 'dual process' theories of the mind (Fudenberg and Levine, 2006;Loewenstein and O'Donoghue, 2007;Kahneman, 2011): System I, which arrives at decision through affective or intuitive processes, and System II, which generates decisions based on deliberative or calculated reasoning (Kahneman, 2003;Evans, 2003Evans, , 2008Loewenstein et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is this joint resultego depletion affects pro-social behavior without affecting pro-social concerns-that represents the key contribution of their paper. We expand on the significance of their results by relating the pattern to recent theorizing about pro-social behavior and the two-stage model of self-control, which distinguishes between identifying self-control conflict and exercising restraint (Martinsson, Myrseth, & Wollbrant, 2012;Kocher, Martinsson, Myrseth, & Wollbrant, 2013;Martinsson, Myrseth, & Wollbrant, 2014).…”
mentioning
confidence: 97%